Pengaruh Model Pembelajaran Kooperatif Tipe TGT Berbantuan Wordwall Terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP - Djanuryanti, Rima; Baidowi, Baidowi; Triutami, Tabita Wahyu (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This study aims to determine the effect of the Teams Games Tournament (TGT) cooperative learning modelassisted by Wordwall on the mathematics learning outcomes of eighth-grade students at SMPN 19 Mataramin the 2025/2026 academic year. The research method used was a quasi-experimental design with a post-testonly control design. The population in this study was eighth-grade students at SMPN 19 Mataram, consistingof six classes. The research sample consisted of class VIII A as the experimental class (applying the TGTmodel assisted by Wordwall) and class VIII C as the control class (applying the direct learning model), whichwere determined using the cluster random sampling technique. The t-test results showed that there was adifference in the average mathematics learning outcomes of students in the experimental class and the controlclass. The average score of the experimental class (79.69) was higher than that of the control class (66.25). Inaddition, the effect size test results were in the large effect category. Thus, it can be concluded that there isan effect of the Teams Games Tournament (TGT) cooperative learning model assisted by Wordwall on themathematics learning outcomes of eighth-grade students at SMPN 19 Mataram in the 2025/2026 academicyear.